(untitled) (Swiss Medical Weekly, 2018)
Dual use research of concern (DURC) is defined by the World Health Organization as “life sciences research that is intended for benefit, but which might easily be misapplied to do harm.” Ethical and policy discussions on DURC span the past three decades. Today, however, new and emerging technologies and associated sociocultural transformations within the scientific community are reshaping the current risk scenario. This paper identifies three major trends that are likely to characterise dual use dilemmas in the near future: the diversification of dual use domains, the digitalisation of potential threats and the proliferation of actors. This analysis illustrates an increasingly heterogeneous and fragmented risk scenario, which can hardly be effectively governed top-down from a centralised authority. We propose that in order to meet the critical challenges of dual use in the 21st century, a global and distributed governance is needed. In contrast to globally binding sets of legal mechanisms administered by a central and hierarchical authority supported by leading powers, we suggest a global and decentralised governance architecture encompassing multilevel, multipolar and bottom-up strategies that can stretch across a spectrum of stakeholders and scientific domains in an agile, proactive and adaptive manner. Finally, we discuss how Switzerland can take a leading role in the promotion and development of this global governance architecture.